STATUS OF MITE PEST FAUNA PREVAILING IN BRINJAL AGRO-ECOSYSTEM - PRASAD, RABINDRA; SINGH, JANARDAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Findings of the field studies on qualitative and quantitative composition of phytophagous mites infesting brinjal, conducted during, 1997 to 2001, in Varanasi region of Uttar Pradesh revealed that brinjal was infested with six mite pest species, viz. Tetranychus urticae, T. macfarlanei, T. ludeni, Brevipalpus phoenicis, Polyphagotarsonemus latus and Aceria lycopersici. Out of these mite species, T. urticae appeared as major pest during post-rainy season, as minor pest in rainy season and as mild pest in autumn. A. lycopersici appeared in the form of mild to severe pest during spring and as extremely severe pest during summer season. T. urticae remained almost absent in presence of heavy incidence of A. lycopersici in spring and Summer seasons on brinjal. The findings indicated that displacement of T. urticae from brinjal by heavy occurrence of A. lycopersici on the same host plant indicated the changing scenario of mite pest spectrum on brinjal in the present studies. As such, T. urticae remained the major mite pest during post-rainy and autumn and A. lycopersici emerged as severe pest during spring and Summer season in brinjal agro-ecosystem in the agro-climatic conditions of Varanasi region.